Assessment of left ventricular contractile reserve during hyperventilation and exercise in patients with ANOCA. (4th February 2022) - Dedic, S; Boskovic, N; Giga, V; Nedeljkovic, I; Tesic, M; Jovanovic, I; Aleksandric, S; Beleslin, B; Ciampi, Q; Picano, E; Djordjevic Dikic, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction. Mechanism of ischemia in patients with angina and no obstructive coronary artery disease (ANOCA), is often unrecognized since invasive tests are seldom done and proper noninvasive test is not established yet. The aim of our study was to assess changes in ventricular function during hyperventilation test (HYP) designed to provoke vasoconstriction, immediately followed by supine bicycle exercise to increase ischemic stimuli in patients with ANOCA (HYP + EXE). Methods. : In a prospective study, we enrolled 29 ANOCA patients (age 59.6 ±11 years, 27 females) with previously normal angiograms. All patients underwent SE testing with hyperventilation (HYP, respiratory rate of 30 per min for 5"), immediately followed by supine bicycle exercise (HYP + EXE). Ventricular function was assessed based on left ventricular contractile reserve (LVCR), calculated by ratio of the ventricular force at the peak of the each stress level and rest. Force was assessed as the quotient between systolic arterial pressure and end-systolic volume determined by two-dimensional echocardiography. Values range from normal (> 2.0) to mild (1.5–2.0), moderate (1.01–1.49), and severe (≤1.0) dysfunction. For LVCR HYP values are shifted towards lower values (abnormal < 1.1). Results. Chest pain or dyspnea were present in 4/29 pts during HYP, and in 7/29 patients during HYP + EXE (13.8% vs 24.1 %, p = 0.001). Three patients showed wall motion abnormalities with hyperventilation and additional two patients with HYP + EXE. LVCR HYP response was normal in 19/29 (65.5%) pts and abnormal in 10/29 (34.5%) pts. LVCR HYP + EXE response was normal in 9/29 (31%) pts, 4/29 (13.8%) pts had mild, 11/29 (37.9%) pts had moderate and 5/29 (17.3%) pts had severe dysfunction. Conclusion. In patients with ANOCA subtle changes in LV function occurred with HYP and EXE stress more often than wall motion abnormality. Measurement of contractile reserve might be a useful tool in assessment of ischemia and ventricular dysfunction in patients with ANOCA.